Panic Buying in Bangladesh: An Exploration of Media Reports - Arafat, S. M. Yasir; Yuen, Kum Fai; Menon, Vikas; Shoib, Sheikh; Ahmad, Araz Ramazan (Frontiers in Psychiatry, 2021)
Background: As an erratic human behavior, panic buying is an under-studied research area. Although panic buying has been reported since long back, it has not been studied systematically in Bangladesh. Aim: It was aimed to see the characteristics of panic buying episodes in Bangladesh in comparison to the current concepts. Methods: A retrospective and explorative search was done in Google on November 06, 2020, with the search term “panic buying in Bangladesh”. All the available news reports published in the English language were extracted. A thorough content analysis was done focusing on the study objectives. Results: From the initial extraction, a total of 30 reports was extracted. However, six reports were dropped after considering the exclusion criteria resulting in the analysis of 24 reports. Five panic buying episodes were identified discussing the precipitating events, responsible factors, goods of panic buying, and prevention measures. Flood, curfew, COVID-19, and export ban were found as precipitating events. Media reports frequently mentioned the prevention strategies, expert opinion, supply chain status, rationing, and government action. The reported goods are necessary for daily living such as rice, oil, spices, and safety products such as hand sanitizer, and mask. Conclusion: The study revealed preliminary findings of panic buying in Bangladesh; however, those are aligned with the current concept of panic buying. Further empirical studies are warranted to see the geographical variation, precise factors, and to test the culturally appropriate controlling measures.